2013
DOI: 10.1136/amiajnl-2012-000917
|View full text |Cite
|
Sign up to set email alerts
|

A practical approach to achieve private medical record linkage in light of public resources

Abstract: Performance of cryptanalysis against BFEs based on patient data is significantly lower than theoretical estimates. The proposed countermeasure makes BFEs resistant to known practical attacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…Restricting the problem further to the set of only the 20 most frequent names, the CSP assigned four of those 20 names correctly. Nevertheless, Kuzu et al (2013) A different and highly successful attack on simple Bloom filters has been published by Niedermeyer et al (2014). Very little computational effort is needed and only publicly available name frequency lists are used for this form of attack.…”
Section: Attacks On Bloom Filtersmentioning
confidence: 99%
See 2 more Smart Citations
“…Restricting the problem further to the set of only the 20 most frequent names, the CSP assigned four of those 20 names correctly. Nevertheless, Kuzu et al (2013) A different and highly successful attack on simple Bloom filters has been published by Niedermeyer et al (2014). Very little computational effort is needed and only publicly available name frequency lists are used for this form of attack.…”
Section: Attacks On Bloom Filtersmentioning
confidence: 99%
“…In their second paper, Kuzu et al (2013) evaluated the practical use of their own attack more critically. Personal identifiers in a given application database such as a medical registry are unlikely to be a random sample of an available population list.…”
Section: Attacks On Bloom Filtersmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuzu et al recently demonstrated an attack that can utilize a global dataset with demographic data (often available publicly) to determine what input strings were used to create the Bloom filter encodings [26]. In a follow up study, the authors demonstrated that the attack is feasible in practice, but the speed and precision of the attack may be worse than theoretical predictions [27]. Methods such as encoding n-grams from multiple identifiers into a single Bloom filter may provide resistance to such attacks, but can adversely impact linkage performance.…”
Section: Related Workmentioning
confidence: 99%
“…Two partially successful attacks on Bloom filters using a Constraint Satisfaction Solver have been reported by [42], [43]. In the more recent study, the authors used combined Bloom filters (a CLK variant).…”
Section: A Security Of Bloom Filter-based Approachesmentioning
confidence: 99%